Education about The Importance of Husband and Family Support Regarding Pregnant Women's Anxiety Trimester III in Facing The Process Labor - Silalahi, Lenny Sepriani; Sipayung, Selamat Tuahta (JURNAL PENGMAS KESTRA (JPK), 2024)
The third trimester of pregnancy is a pregnancy that requires vigilance. At this time, pregnant women often experience anxiety about the condition of their baby, which will be born normally or abnormally. Support from her husband and family is something that a mother needs to relieve her anxiety. The main target of this outreach is people in the area This is due to the lack of support given by the husband and family to pregnant women before the birth process. This counseling aims to provide education to husbands and families to provide attention and support to pregnant wives or families so that they do not experience anxiety in facing the birthing process. The targets for this outreach activity are husbands and families (parents) who have wives or children who are in the third trimester of pregnancy. To assess husband and family support, it will be carried out twice, namely asking questions before and after counseling. The results obtained indicate that there is a change in attitude in the form of support for pregnant wives or families before and after being given counseling. This is a good way to overcome problems related to third trimester pregnancy in the health environment.